KUNJUNGAN LEBAH TUKANG KAYU Xylocopa confusa Linn. (HYMENOPTERA: ANTHOPHORIDAE) PADA PERTANAMAN MENTIMUN DI KELURAHAN SURAU GADANG KECAMATAN NANGGALO KOTA PADANG - Azmi, Ulul - (Pendidikan Biologi, 2014)
Insects have important value, as well as insects harmfull or helpfull one of the visitors was a group of insects is Xylocopa confusa often referred to as a carpenter bee. These bees eat pollen and nectar. One of the plants that are frequented by Xylocopa confusa is cucumber. Cucumber ia annual plant that is herbs climbed. Based on this research aimed to determine the number of visits and the number of flowers visited by Xylocopa confusa on planting cucumber at Surau Gadang Nanggalo District Padang City.The research was conducted in February-Maret 2014. Observations and sample calculations perfomed in Surau Gadang Kecamatan Nanggalo. Padang. The method used was a descriptive survey method that is by directly observing the insects that exist in the location of research. Insect observations made at 06.00-18.00 WIB. In this study were analyzed by regression analysis of variance multiple and environmental factors with multiple regression. From the result of the study showed that the amount of Xylocopa confusa most widely visited in the morning at 09.15-09.30 WIB with averaged 12,57 individu and the last visited in the afternoon at 13.15-13.30 WIB with averaged 1,43 individu. Xylocopa confusa exit from planting cucumber most at 09.15-09.30 WIB with averaged 8,86 tail and the last visited the afternoon at 13.15-13.30 WIB with averaged 1,43 individu. The amount of interest the most visited Xylocopa confusa in the morning averaged 10,04 of flowers and the last in the afternoon averaged 6,76 of flowers. The environmental parameters are temperature, humidity, and wind speed not significant affect the number of visits Xylocopa confusa on planting cucumbers but light intensity significant affect the number of visits Xylocopa confusa on planting cucumbers. Based on the results of the regression multiple relationship during the observations obtained that wind speed significant affect of visits Xylocopa confusa on planting cucumber in Surau Gadang Nanggalo district Padang City.